Methods of aircraft trajectory optimisation in air combat - Nusyirwan, Istas Fahrurrazi; Bil, Cees (Australian Mathematical Society Inc., 2007)
We overview methodologies to optimise an aircraft trajectory in a two-player close air combat scenario. In mathematical terms air combat can be considered as a game. However, due to the highly nonlinear equations of motion involved, the use of classical games theory is difficult to implement in a computer simulation. The search for the saddle point of the game is difficult and therefore an indirect approach is required to search for the best trajectory. At each instance, one player is given the role of evader and the other the pursuer. The evader must find the trajectory that avoids or maximises the time to interception, while the pursuer must find a trajectory that achieves or minimises the time to intercept the evader. An algorithm has been developed and implemented using Evolutionary Programming. Simulations show that the algorithm is able to find good individuals (or solutions) in a limited time.